Opredelitev strateškega komuniciranja - Hallahan, Kirk (Teorija in praksa, 2008)
This article explores the nature of strategic communication, which is defined as the systematic use of communication by the organization to fulfill its mission. With the development, implementation and evaluation of communication within the organization is engaged six disciplines: management, marketing, public relations, technical communication, political communication and information oz. social-marketing campaign. Article also discussed the nature of the term "strategic" and present key aspects of communication. Partly based on the authors and other participants contributions at the International Communication Association (ICA) roundtable in May 2005 in New York.
Keywords: Communication; Komuniciranje; Komunikacijsko upravljanje; Communication management; Communication model; Komunikacijski modeli; Communication theory; Teorija komuniciranja; Public relations; Odnosi z javnostmi; strateško komuniciranje; organizacijsko komuniciranje; organizacije